Food handler’s behavioral intention to practice safe food handling in franchise restaurant / Wan Hayati Wan Bujang - Wan Bujang, Wan Hayati (2012)
Food safety problems can occur at any stage of a food system and the restaurant will be the last point in the sequence from farm to fork as food is processed, cooked and finally served to the customers. Ironically, restaurants have been detected as one of the most common places for food-borne illness outbreaks. It has been detected by World Health Organization (2006) that there are five major factors lead to lead to food borne illness, which includes lack of hygiene and sanitation by the food handlers; improper cooking procedures; temperature abuse during storage; crosscontamination between fresh ready-to-eat foods and raw foods; and, acquiring food from risky sources. A mistake in handling foods by the individuals was recognized as the major reason for outbreaks of food poisoning. This study was conducted to explore the factors influence the food handlers‟ intention to practice safe food handling at the restaurants. It is important to investigate the attitude, social factor and perceived behavioural control towards food handler‟s behavioural intention. For this study, the Theory of Planned Behaviour was used to evaluate the impacts and influences of attitude, subjective norm, and perceived behaviour on the intention and behaviour of the food handlers. 33 outlets of franchise restaurants in Shah Alam, Selangor cooperate in this study. 144 food handlers involved as the respondents in this study. Data of the study were collected through self-administered survey questionnaires. For the data analysis, descriptive analysis, reliability analysis, and multiple regression analysis were used in this study. Based on the statistical result, the highest standardized beta coefficient was perceived behavioural control (β=0.345, p=0.000) and this determined that perceived behavioural control as the largest influences and makes the strongest predictor for the behavioural intention. This explained that perceived behavioural control was the best predictor influenced the food handler behavioural intention in practicing safe food handling for every occasion at the restaurant. Both subjective norm and perceived behavioural control were significant to predict the food handlers‟ behavioural intention but attitude was not significant. Finally, the result of this study created new finding and develop understanding in term of factors leads to behavioural intention in practicing safe food handling at the restaurant. Some of recommendation has been made in effort to improve the behavioural intention among food handlers to practice safe food handling for future research in different foodservice establishment.